Miniaturized Sierpinski fractal loaded QMSIW antenna with CSRR in ground plane for WLAN applications. Issue 6 (30th March 2017) - Choudhury, Suvadeep; Mohan, Akhilesh
ABSTRACT: In this paper, electrically small substrate integrated waveguide (SIW) antenna based on Sierpinski fractal and complementary split ring resonators (CSRR) are proposed. The antenna size is electrically reduced by the use of quarter‐mode substrate integrated waveguide (QMSIW) and Sierpinski fractals. The CSRR added on the ground plane introduces additional inductance and capacitance to the overall structure to further reduce the size. The overall size of the proposed antenna is 23 mm × 20.5 mm. The resonant frequency for the first mode of the antenna is tuned by rotating the CSRR structure, while maintaining almost identical radiation pattern and performance. The S‐parameters and radiation characteristics have been investigated by full‐wave EM‐simulation and measurement. For the first mode, the resonant frequency varies from 4.96 GHz to 5.88 GHz by the rotation of CSRR structure from 0° to 315° making it suitable for IEEE 802.11 WLAN applications. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1291–1295, 2017